Menu Recognition Using Rendered Webpage Information and Machine Learning - Choi, Chan; Park, Minwoo; Jung, Geunseong; Cha, Jaehyuk (International Journal of Engineering and Technology, 2019)
Among the many components of a webpage, the web menu provides organization as well as information on the primary content of the website. By recognizing the menu existing within a webpage, it is possible to identify the overall structure of the website from the menu's information for crawling and indexing. Therefore, tasks can be performed efficiently without accessing the pages unnecessarily. In addition, a variety of applications could be developed through web menu detection. This paper suggests a method to categorize the web menu within a webpage using machine learning. Rendered attribute values of the web document are extracted with processed data to offer more choices in selecting the machine learning attributes. This paper also proposes and demonstrates a Chrome extension-based webpage document collector that effectively collects the final rendered form of a webpage in a browser and its internal data that are required when performing machine learning for web menu categorization. Lastly, a demo platform that can detect webpage menus in real time is designed based on the learned result.Â Â